The mediating effect of attitude on E-Wallet usage among users in Malaysia - Abdul Kadir, Hasnah; Ismail, Rizalawati; Wok, Saodah; Abdul Manan, Kamaruzzaman (Malaysian Association of Educators (MACE), 2022)
Malaysia is moving towards a cashless society. The latest trend in a cashless society is e-Wallet, which has the ability to store personal information as well as financial status. The e-Wallet can efficiently replace the physical wallet (cash). The implementation of online Internet banking for a financial transaction is the starting point of e-Wallet in Malaysia. In 2017, e-Wallet is introduced to the public. This study tries to gauge the extent of e-Wallet usage in Malaysia. The objectives of the study are to (1) determine the level of usage, perceived usefulness, perceived ease-of-use, media influence, social influence, and attitude in using e-Wallet; (2) analyse the relationship between e-Wallet usage with internal and external factors; and (3) test mediating effect of attitude in using e-Wallet on the relationship between usage, internal factors, and external factors. The study uses a quantitative research design using a survey method with the questionnaire as the research instrument. A total of 436 respondents participated in the study. The study uses Technological Acceptance Model (TAM) to test for the mediating effect. The findings show that perceived ease-of-use is the highest level rated compared to other variables. The relationship between e-Wallet usage with the internal and external factors are all significant and positive. Furthermore, the attitude partially mediates the relationship between e-Wallet usage, internal factors and external factors. Hence, all hypotheses constructed are supported and TAM applies to the study of e-Wallet.